1994
DOI: 10.1051/lait:1994314
|View full text |Cite
|
Sign up to set email alerts
|

Croissance des bactéries propioniques dans le fromage : comparaison de 2 milieux de dénombrement

Abstract: (Reçu le 12 janvier 1994; accepté le 11 février 1994) Résumé -La cinétique de croissance de flores propioniques «sauvages» ou réensemencées a été étudiée au cours de l'affinage de mini-fromages de type emmental. Le dénombrement des bactéries propioniques dans des fromages de flore de complexité variable a été effectué de manière comparative sur les milieux LGA (lithium-glycérol-agar) et YELA (yeast-extract-Iactate-agar). La diversité de la population propionique a été appréciée par la comparaison des profils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
2
6
0
3
Order By: Relevance
“…The growth parameters of both PAB strains in Emmental cheese juice were in agreement with those previously observed by Salvat-Brunaud et al [32], and close to those found in experimental cheese [36] and in French industrial Emmental [37]. Moreover, kinetics of lactate consumption fitted well with the molar ratio given by the Fitz equation [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The growth parameters of both PAB strains in Emmental cheese juice were in agreement with those previously observed by Salvat-Brunaud et al [32], and close to those found in experimental cheese [36] and in French industrial Emmental [37]. Moreover, kinetics of lactate consumption fitted well with the molar ratio given by the Fitz equation [13].…”
Section: Discussionsupporting
confidence: 90%
“…All the microbiological measurements were made in duplicate by means of a Spiral system apparatus (DS model Interscience, Saint-Nomla-Bretèche, France), except PAB, added into the agar plates. PAB were enumerated on LGA medium after 6 d incubation at 30 o C under anaerobiosis (anaerocult A, Merck) [36]. Flora growing during crude juice incubation were determined as follows: total mesophilic aerobic flora was assessed on Plate Count Agar (Biokar) after incubation for 3 d at 30 o C. FHL were enumerated on FH medium incubated for 3 d at 37 o C under anaerobiosis [17].…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Propionibacteria were enumerated on lithium-glycerol agar [42] incubated at 30°C anaerobically for 6 d. Non-starter lactic acid bacteria, which can grow in cheeses during the ripening, were enumerated on FH agar [20] incubated at 30°C anaerobically for 3 d and on MRS agar incubated at 15°C anaerobically for 14 d [46].…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…téries propioniques ont été dénombrées sur les milieux LGA et Pal Propiobac [48,49] incubés 6 jours à 30 "C en anaérobiose. Les lactobacilles hétérofermentaires ont été dénombrés après incubation 72 h à 37 "C en anaérobiose sur le milieu FH [26], sur lequel les colonies typiques comme atypiques ont été dénombrées.…”
Section: Analyses Microbiologiquesunclassified
“…Les bactéries propioniques se développaient essentiellement en cave chaude, avec un temps de génération maximal d'environ 35-42 h, voisin de celui relevé dans des fabrications expérimentales [48]. Malgré une population initiale différente dans les trois séries, leur population finale atteignait 8,0 à 8,6 logjufc-g') (figure 1).…”
Section: éVolution Des Levains Propioniquesunclassified